Retinal pharmacodynamic and pharmacokinetic profile of cannabidiol in an in vivo model of retinal excitotoxicity - Conti, Federica; Lazzara, Francesca; Thermos, Kyriaki; Zingale, Elide; Spyridakos, Dimitris; Romano, Giovanni Luca; Di Martino, Serena; Micale, Vincenzo; Kuchar, Martin; Spadaro, Angelo; Pignatello, Rosario; Rossi, Settimio; et al. (European journal of pharmacology, 2025)
Cannabidiol (CBD) is one of the principal constituents of Cannabis Sativa with no psychoactive properties. CBD is a promising neuroprotective compound bearing anti-inflammatory and antioxidant properties. However, considering its low solubility, CBD delivery to the retina represents an unresolved issue. The first aim was to investigate the potential neuroprotective effects of CBD in an in vivo model of retinal excitotoxicity induced by α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA). Rats underwent intravitreal co-injection of AMPA (42 nmol) and CBD (10-4 M). The neuroprotective effect of CBD was investigated with histology and immunohistochemical evaluation of inflammatory and oxidative stress biomarkers. CBD reversed the AMPA-induced total retinal, inner nuclear layer and inner plexiform layer shrinkage and loss of amacrine cells. Moreover, CBD decreased the AMPA induced number of cleaved caspase-3, Iba-1 and nitrotyrosine (NT) positive cells. Based on this evidence, we developed a nanotechnological formulation of CBD to overcome critical issues related to its eye delivery. Particularly, nanostructured lipid carriers (NLC) loaded with CBD were prepared, optimized and characterized. Due to the optimal physicochemical characteristics, CBD-NLC3 has been selected and the in vitro release profile has been investigated. Additionally, CBD-NLC3 was topically administered to rats, and retinal CBD levels were determined. CBD-NLC3 formulation, after a single topical administration, efficiently delivered CBD in the retina (Cmax = 98 ± 25.9 ng/mg; Tmax = 60 min), showing a high translational value. In conclusion, these findings showed a good PD/PK profile of CBD warranting further pre-clinical and clinical evaluation of the new formulation for the treatment of retinal degenerative diseases.
Keywords: kaspasa 3; Animals; kyselina alfa-amino-3-hydroxy-5-methyl-4-isoxazolpropionová; Rats, Wistar; oxidační stres; Retina; Calcium-Binding Proteins; Oxidative Stress; mikrofilamentové proteiny; Drug Carriers; Tyrosine; proteiny vázající vápník; Male; modely nemocí na zvířatech; Neuroprotective Agents; Cannabidiol; Disease Models, Animal; krysa rodu Rattus; nosiče léků; tyrosin; Caspase 3; retina; mužské pohlaví; zvířata; kanabidiol; alpha-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid; Microfilament Proteins; Rats; potkani Wistar; neuroprotektivní látky